THE THE EFFECT OF MUDHARABAH FINANCING AND MUSYARAKAH FINANCING ON NET PROFIT AT BCA SYARIAH 2018-2020 - Hafidzah Misdalifah; Wirman . (UNHI Press, 2022)
: This study was conducted with the aim of knowing and analyzing the simultaneous and partial effect of mudharabah financing and musyarakah financing on BCA Syariah net income for the 2018-2020 period. This study uses a quantitative approach with secondary data in the form of monthly financial statements for the company for three years. Statistical calculations in this study used SPSS 16 with the classical assumption test, namely: normality test, mutilinearity test, autocorrelation test, and heteroscedasticity test. Hypothesis testing using f test, t test, and coefficient of determination. The results of the research conducted show that: 1) Mudharabah financing has no effect on net income. 2) Musyarakah financing partially has an effect on net income. 3) mudharabah financing and musyarakah financing simultaneously or simultaneously affect net profit at BCA Syariah for the 2018-2020 period